2018
DOI: 10.3389/fmars.2017.00430
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Chromophoric Dissolved Organic Matter by Bacterial Degradation of Phytoplankton-Derived Aggregates

Abstract: Organic matter produced and released by phytoplankton during growth is processed by heterotrophic bacterial communities that transform dissolved organic matter into biomass and recycle inorganic nutrients, fueling microbial food web interactions. Bacterial transformation of phytoplankton-derived organic matter also plays a poorly known role in the formation of chromophoric dissolved organic matter (CDOM) which is ubiquitous in the ocean. Despite the importance of organic matter cycling, growth of phytoplankton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 74 publications
(105 reference statements)
7
53
0
Order By: Relevance
“…The depth of this subsurface maximum z YSM is highly correlated to z DCM in the central basin (Figure 7b), and also in the northern SCS, except for the winter-spring period (Figure 7a). This phenomenon was observed in the Mediterranean Sea and suggests that FDOM was biologically controlled, either directly produced by phytoplankton (exudates; Fukuzaki et al, 2014;Romera-Castillo et al, 2010) or via phytoplankton-affected bacterial activity (Rochelle-Newall & Fisher, 2002;Kinsey et al, 2018). The decoupling (winter-spring) only appeared in the northern basin where winter mixing was strong and the DCM eroded, with a weak YSM (dFDOM <0.2 ppb, Figure 7c); in the spring, the coupling was rebuilt after the subsurface waters restratified, and FDOM began to accumulate from March.…”
Section: Relationship Of Fdom and Chlorophyll-a Distributionmentioning
confidence: 94%
“…The depth of this subsurface maximum z YSM is highly correlated to z DCM in the central basin (Figure 7b), and also in the northern SCS, except for the winter-spring period (Figure 7a). This phenomenon was observed in the Mediterranean Sea and suggests that FDOM was biologically controlled, either directly produced by phytoplankton (exudates; Fukuzaki et al, 2014;Romera-Castillo et al, 2010) or via phytoplankton-affected bacterial activity (Rochelle-Newall & Fisher, 2002;Kinsey et al, 2018). The decoupling (winter-spring) only appeared in the northern basin where winter mixing was strong and the DCM eroded, with a weak YSM (dFDOM <0.2 ppb, Figure 7c); in the spring, the coupling was rebuilt after the subsurface waters restratified, and FDOM began to accumulate from March.…”
Section: Relationship Of Fdom and Chlorophyll-a Distributionmentioning
confidence: 94%
“…It is now well documented that bacterial communities have the ability to degrade and/or generate various types of fluorescent compounds. Although considered recalcitrant and mainly from terrestrial origin, consumption (Moran et al 2000;Romera-Castillo et al 2011;Fasching et al 2014) as well as production (Guillemette and del Giorgio 2012;Amaral et al 2016;Kinsey et al 2018) of humic-like components by heterotrophic bacteria have been previously reported. Similarly, proteinaceous compounds are considered as a highly labile pool of FDOM (Fellman et al 2009a;Cory and Kaplan 2012) but net production of protein-like fractions during bioassays have also been reported elsewhere (Cammack et al 2004;Lønborg et al 2009;Guillemette and del Giorgio 2012).…”
Section: Non-conservative Effects On Dom Degradationmentioning
confidence: 99%
“…Higher concentrations of C4 are commonly reported in productive waters, such as coastal upwelling regions and at mid-salinities in some estuaries (Coble et al, 1998;Fellman et al, 2010b). This component can be produced by bacterial reprocessing of fresh phytoplankton-derived organic matter (Kinsey et al, 2018), but also directly by phytoplankton in the absence of bacteria (Romera-Castillo et al, 2010). However, in this study, because C4 showed such a close correlation with C1 and C2, but not with chlorophyll-a or C5, we inferred that C4 was unlikely to be associated with aquatic primary production.…”
Section: Fdom Markers As Tracers Of Dom Sources In Sarawakmentioning
confidence: 99%
“…High concentrations of protein-like components are typically reported during algal blooms, and are generally thought to trace fresh, autochthonous DOM in fresh-and seawater (Stedmon and Markager, 2005;Murphy et al, 2008;Jørgensen et al, 2011). C5 is produced by phytoplankton cultures (Kinsey et al, 2018;Romera-Castillo et al, 2010), but production rates vary between phytoplankton species (Fukuzaki et al, 2014). Furthermore, Yamashita et al (2015) found that a protein-like component was indicative of the bioavailability of DOM, correlating strongly with DOC-normalized amino acid yields.…”
Section: Fdom Markers As Tracers Of Dom Sources In Sarawakmentioning
confidence: 99%